Can SUSY relax lepton number violation constraints coming from loop corrections to light neutrino masses on the low-scale seesaw mechanism - Jones-Pérez, J.; Suarez-Navarro, O. (American Physical Society, 2023)
Heavy neutrinos from the type-I seesaw model can have a large mixing with active states, motivating their search at collider experiments. However, loop corrections to light neutrino masses constrain the heavy neutrinos to appear in pseudo-Dirac pairs, leading to a potential suppression of lepton number violating parameters. In this work we perform a detailed review of a proposal to relax constraints on lepton number violation by adding supersymmetry (SUSY). We define the conditions necessary to maximize the SUSY screening effect, with the objective of allowing a larger mass splitting between low-scale heavy neutrino masses. We find that the sole addition of SUSY does not guarantee a screening, and that favorable cases have some degree of fine-tuning.
Keywords: Physics; Particle physics; Seesaw molecular geometry; Neutrino; Seesaw mechanism; Supersymmetry; Lepton; Lepton number; Physics beyond the Standard Model; Collider; Neutrino oscillation; Sterile neutrino; Nuclear physics; Electron; https://purl.org/pe-repo/ocde/ford#1.03.03